RNAi-mediated down-regulation of the expression of OsFAD2-1: effect on lipid accumulation and expression of lipid biosynthetic genes in the rice grain. Issue 1 (December 2016) - Tiwari, Gopal; Liu, Qing; Shreshtha, Pushkar; Li, Zhongyi; Rahman, Sadequr
Abstract Background The bran from polished rice grains can be used to produce rice bran oil (RBO). High oleic (HO) RBO has been generated previously through RNAi down-regulation ofOsFAD2-1 . HO-RBO has higher oxidative stability and could be directly used in the food industry without hydrogenation, and is hence free oftrans fatty acids. However, relative to a classic oilseed, lipid metabolism in the rice grain is poorly studied and the genetic alteration in the novel HO genotype remains unexplored. Results Here, we have undertaken further analysis of role ofOsFAD2-1 in the developing rice grain. The use of Illumina-based NGS transcriptomics analysis of developing rice grain reveals that knockdown ofOs-FAD2-1 gene expression was accompanied by the down regulation of the expression of a number of key genes in the lipid biosynthesis pathway in the HO rice line. A slightly higher level of oil accumulation was also observed in the HO-RBO. Conclusion Prominent among the down regulated genes were those that coded for FatA, LACS, SAD2, SAD5, caleosin and steroleosin. It may be possible to further increase the oleic acid content in rice oil by altering the expression of the lipid biosynthetic genes that are affected in the HO line.